2015
DOI: 10.1155/2015/153015
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Biological Evaluation of New Hydrazone Derivatives of Quinoline and Their Cu(II) and Zn(II) Complexes againstMycobacterium tuberculosis

Abstract: A new series of quinoline hydrazone derivatives and their metal complexes have been synthesized and their biological properties have been evaluated against Mycobacterium tuberculosis (H37 RV strain). Most of the newly synthesized compounds displayed 100% inhibitory activity at a concentration of 6.25–25 μg/mL, against Mycobacterium tuberculosis. Fluorescence properties of all the synthesized compounds have been studied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(25 citation statements)
references
References 18 publications
2
23
0
Order By: Relevance
“…Our results of the copper(II) complexes loaded into the NLCs showed better tuberculostatic activity against M. tuberculosis H 37 R v than the values reported by Mandewale et al,48 wherein the copper(II) complexes bound to hydrazone ligands showed MIC values ranging from 6.25–12.5 μg/mL and the free ligands displayed MIC values from 25–50 μg/mL.…”
Section: Resultssupporting
confidence: 51%
“…Our results of the copper(II) complexes loaded into the NLCs showed better tuberculostatic activity against M. tuberculosis H 37 R v than the values reported by Mandewale et al,48 wherein the copper(II) complexes bound to hydrazone ligands showed MIC values ranging from 6.25–12.5 μg/mL and the free ligands displayed MIC values from 25–50 μg/mL.…”
Section: Resultssupporting
confidence: 51%
“…Additionally, quinolines are considered as an interesting group of compounds, many of which have widespread pharmacologicalactions such as anti-microbial, [1][2][3][4] anti-inflammatory, [5][6][7][8] antitubercular, [9][10][11][12] anti-convulsant, [13] antihypertensive, [14,15] antioxidant, [16][17][18][19] and anticancer [20] activities. Nitrones can release nitric oxide in larger amounts compared to corresponding oximes.…”
mentioning
confidence: 99%
“…actions such as anti-microbial, [1][2][3][4] anti-inflammatory, [5][6][7][8] antitubercular, [9][10][11][12] anti-convulsant, [13] antihypertensive, [14,15] antioxidant, [16][17][18][19] and anticancer [20] activities. Several mechanisms can explain the anticancer effect of quinoline derivatives including: topoisomerase inhibition, [21][22][23] DNA intercalation, [24] protein kinases inhibition, [25][26][27] tubulin polymerase inhibition, [28][29][30][31] and induction of apoptosis.…”
mentioning
confidence: 99%
“…This causes an increase in -electron delocalization throughout the coordination ring. This results in increased metal complex lipophilicity [56]. Therefore, research on flavonoid metal complexes is very helpful in developing new TB drugs.…”
Section: Bioinorganic Chemistry Associated With Radical Scavenging Acmentioning
confidence: 99%